The role of APOE gene polymorphisms in lung adenocarcinoma susceptibility and lipid profile - Bi, Huanhuan; Ren, Dunqiang; Wang, Ye; Wang, Hongmei; Zhang, Chunling (Frontiers in Immunology, 2024)
BackgroundAPOE gene polym orphisms have been linked to Alzheimer’s disease and coronary heart diseases. However, their relationship with lung adenocarcinoma (LUAD) remains uncertain.MethodsThis study analyzed a cohort of 600 individuals comprising 200 LUAD patients in the lung cancer group and 400 healthy individuals as controls. APOE gene variants were identified through Sanger sequencing. Statistical analyses were conducted to assess intergroup differences, and comparisons of lipid profiles were performed across individuals carrying different APOE alleles.ResultsThe APOE ϵ2 allele had been significantly more frequently occurring in the LUAD group than in the control group (15.5% vs. 7%, P <0.001). APOE ϵ2/ϵ2 and ϵ2/ϵ3 genotypes increased susceptibility to LUAD by 3.78-fold and 3.22-fold. The APOE ϵ2/ϵ3 genotype increased the risk of early-stage LUAD by 2.36-fold and advanced-stage LUAD by 4.05-fold. Individuals with the APOE ϵ2/ϵ2 genotype had a 3.22-fold higher susceptibility to moderately differentiated and a 6.8-fold higher susceptibility to poorly differentiated LUAD. Patients with the ϵ2 allele in LUAD exhibited disrupted lipid metabolism, characterized by reduced HDL, TC, and FFA levels, along with increased ApoB, particularly in advanced and poorly differentiated cancer stages.ConclusionIndividuals carrying the ϵ2 allele have an increased susceptibility to developing LUAD, accompanied by disrupted lipid metabolism. Additionally, the APOE ϵ2/ϵ2 and ϵ2/ϵ3 genotypes are associated with an increased risk of developing advanced and poorly differentiated LUAD.